Muhammadiyah: Modernisasi Islam dan Pemberdayaan Sosial di Indonesia - M. Alfazri; Muhammad Anshori (PT. Intelek Cendikiawan Nusantara, 2024)
Muhammadiyah, founded in 1912, is one of the largest Islamic organizations in Indonesia, playing a significant role in the modernization of Islam and social empowerment. The organization focuses on preaching based on the Qur'an and Hadith, along with various social initiatives in education, healthcare, and welfare. Muhammadiyah has established educational institutions ranging from primary schools to universities and manages hospitals, clinics, and health centers to serve the community. Additionally, it operates orphanages, homes for the elderly, and rehabilitation centers. As an Islamic reform movement, Muhammadiyah integrates religious values with social aspects of life to empower communities and elevate the nation's dignity. This study explores Muhammadiyah's contributions to the modernization of Islam and social empowerment in Indonesia, as well as its role in supporting positive change and community development.